Projekty turystyczne - istota, rodzaje, opłacalność - Kołakowski, Tomasz (Definition, Types and Effectiveness of Tourism Projects, 2008)
Nowadays the words "project" and "tourism" are one of the most popular. What is more, that two terms are often merged and collocation "tourism project" seems to be very fashionable. Therefore in the first part of the article the word "project" is showed in the management and economy development approach. Moreover, the paper presents the meaning of the term "tourism project" and some information about its types. In the second part of the article, general approach to the financial and economic analysis of that project is presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 125-132